2021
DOI: 10.3389/fpls.2020.596065
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Comparison of the Developmental/Physiological Phenotype and the Molecular Behavior of SPIRRIG Between Arabidopsis thaliana and Arabis alpina

Abstract: Beige and Chediak Higashi (BEACH) domain proteins mediate membrane-dependent processes in eukaryotic cells. The plant BEACH domain protein SPIRRIG in A. thaliana (AtSPI) was shown to display a similar molecular behavior as its yeast and animal homologs, along with a range of cell morphological defects. In addition, AtSPI was shown to interact with the P-body component DCP1, to differentially effect RNA levels and to be involved in the regulation of RNA stability in the context of salt stress responses. To dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Two short root hair mutants had STOP codons in SPIRRIG (SPI) at positions 2,107 and 1976, similar to Atspi-4.2 (Saedler et al, 2009; Figure 4I; Supplementary Figure S1I). Four spi alleles in A. alpina with similar phenotypes have been previously reported (Chopra et al, 2019;Stephan et al, 2021). In four short root hair mutants, we found meaningful SNPs in the CAN OF WORMS 1 (COW1) gene (Grierson et al, 1997;Böhme et al, 2004;Figure 4J; Supplementary Figure S1J).…”
Section: Root Hair Morphology Mutantssupporting
confidence: 76%
“…Two short root hair mutants had STOP codons in SPIRRIG (SPI) at positions 2,107 and 1976, similar to Atspi-4.2 (Saedler et al, 2009; Figure 4I; Supplementary Figure S1I). Four spi alleles in A. alpina with similar phenotypes have been previously reported (Chopra et al, 2019;Stephan et al, 2021). In four short root hair mutants, we found meaningful SNPs in the CAN OF WORMS 1 (COW1) gene (Grierson et al, 1997;Böhme et al, 2004;Figure 4J; Supplementary Figure S1J).…”
Section: Root Hair Morphology Mutantssupporting
confidence: 76%
“…This indicates that SPI has a dual role in membrane trafficking and RNA metabolism. Recently, the analysis of SPI in Arabis alpina has provided evidence that this dual role might be evolutionarily conserved (Stephan et al, 2021 ). These findings raise the question, whether other ESCRT proteins, or endosomal sorting in general, are associated with mRNA pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The BEACH domain proteins in eukaryotes cluster into four groups (A-D; Saedler et al, 2009) with similar domain structures (Supplementary Figure S1). AtSPI belongs to group A and is well conserved throughout the plant kingdom (Supplementary Figure S1; Stephan et al, 2021). Group A members share a Laminin G/Concanavalin A superfamily domain but lack additional domains found in the other groups.…”
Section: Resultsmentioning
confidence: 99%
“…Evolutionary comparison of SPI between A. thaliana and Arabis alpina demonstrated that the role of SPI in cell morphogenesis and endosomal pathways is conserved between these two Brassicaceae species (Stephan et al, 2021). This is evident from SPI co-localization and interaction with ESCRT components and a similar range of phenotypes.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation